2006
DOI: 10.1021/ol052862g
|View full text |Cite
|
Sign up to set email alerts
|

Torsional Steering Controls the Stereoselectivity of Epoxidation in the Guanacastepene A Synthesis

Abstract: The stereoselectivity of the key epoxidation step in the synthesis of Guanacastepene A is shown to be controlled by torsional steering. In this particular epoxidation reaction, the transition structure energetic difference is enhanced by the great asynchronicity of the forming C-O bonds that intensifies the torsional interactions.The stereoselective epoxidation of the Guanacastepene A precursor 1 constitutes a key step which provides the correct stereochemistry of the β-acetoxy ketone, as shown above. 1 Cursor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
1
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 19 publications
5
29
1
2
Order By: Relevance
“…The chair conformers of these bicyclic rings contain two pairs of eclipsing interactions between a pseudoaxial C–H bond in the five-membered ring (as shown in Fig. 3, A for 4a ) and either an N + –R bond or a C–H bond at one of the ring junctions (not shown), as documented previously [2729]. When C(4) is fluorinated, the so-called electrostatic gauche effect [30][31], i.e.…”
Section: Resultssupporting
confidence: 80%
“…The chair conformers of these bicyclic rings contain two pairs of eclipsing interactions between a pseudoaxial C–H bond in the five-membered ring (as shown in Fig. 3, A for 4a ) and either an N + –R bond or a C–H bond at one of the ring junctions (not shown), as documented previously [2729]. When C(4) is fluorinated, the so-called electrostatic gauche effect [30][31], i.e.…”
Section: Resultssupporting
confidence: 80%
“…9 Danishsky’s group showed that the epoxidation of guanacastepene A precursor 5 , which consists of a fused cyclopentene, takes place exclusively from the β–face to give β–epoxide 6 as the major product. 35 This is surprising since it appears from the drawing of 5 , that the i Pr and Me substituent should block the β–face.…”
Section: Stereoselectivities Of Reactions Of Cyclopentene Systemsmentioning
confidence: 99%
“…9 Torsional effects steer the reactant to approach the π-system in a manner that minimizes eclipsing interactions at the reaction center. The importance of a staggered arrangement with respect to forming bonds was first identified by Felkin in 1968 for nucleophilic additions to cyclohexanones.…”
Section: Introductionmentioning
confidence: 99%
“…This intriguing stereoselectivity was the subject of computational studies performed by Houk, Danishefsky and coworkers. 89 The corresponding transition structures and energies leading to the a-and b-selectivities were calculated employing density functional theory investigations as shown in Scheme 23. Because of the eclipsing interactions, the a-epoxidation transition structure 192a is less stable by 2.6 kcal mol À1 compared to staggered transition structure 192b for b-epoxidation, as shown by the Newman projections.…”
Section: Computational Studiesmentioning
confidence: 99%